2021
DOI: 10.9778/cmajo.20210013
|View full text |Cite
|
Sign up to set email alerts
|

Physician perspectives on delays in cancer diagnosis in Alberta: a qualitative study

Abstract: Background: Delays in cancer diagnosis have been associated with reduced survival, decreased quality of life after treatment, and suboptimal patient experience. The objective of the study was to explore the perspectives of a group of family physicians and other specialists regarding potentially avoidable delays in diagnosing cancer, and approaches that may help expedite the process. Methods:We conducted a qualitative study using interviews with physicians practising in primary and outpatient care settings in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In alignment with current discussions on suboptimal care continuity and inconsistent collaboration between family physicians or specialists, 5 , 9 , 48 , 49 our findings emphasize the importance of pathways, while also suggesting the need for additional improved supports for family physicians. A previous study by this team 1 reported that family physicians and cancer specialists supported the implementation of a centralized service where primary and specialist physicians converge in their roles. Pathways, low-risk guides and other initiatives, such as rapid access clinics 50 , 51 and specialty teleconsultation systems, 15 could be considered.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In alignment with current discussions on suboptimal care continuity and inconsistent collaboration between family physicians or specialists, 5 , 9 , 48 , 49 our findings emphasize the importance of pathways, while also suggesting the need for additional improved supports for family physicians. A previous study by this team 1 reported that family physicians and cancer specialists supported the implementation of a centralized service where primary and specialist physicians converge in their roles. Pathways, low-risk guides and other initiatives, such as rapid access clinics 50 , 51 and specialty teleconsultation systems, 15 could be considered.…”
Section: Discussionmentioning
confidence: 98%
“…Interview guides were developed by the research team, which included a family physician and 2 allied health professionals, and based on practice expertise and previous work in the area. 1 , 18 , 33 , 34 In addition, we pilot-tested the interview guide with an external family physician. Interviews were conducted by an interviewer and a note-taker, both members of the AMA Accelerating Change Transformation Team (AMA-ACTT) trained in cognitive task analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted in-depth, semi-structured interviews. Two authors (APB and AW) developed the interview guides based on the literature, insights from previous studies examining perspectives of both patient and healthcare providers (31,32), and feedback received from two patient advisors. The interview topics are presented in Table 1.…”
Section: Data Collectionmentioning
confidence: 99%